Robot‐assisted laparoscopic (RAL) surgery for gastric cancer. Issue 3 (23rd December 2013) - Alimoglu, Orhan; Atak, Ibrahim; Eren, Tunc
Abstract Background This literature review focuses on the potential benefits and eventual limitations of robotic surgery with respect to the traditional minimally invasive laparoscopic surgical technique for gastric cancer. Methods A literature survey was performed using specific search phrases in PubMed. Series including < 10 cases and series including only an 'open group' of patients in comparison with the 'robotic group' were excluded. Characteristics such as patient demographics, perioperative outcomes and oncological results were analysed. Results According to the analysis of 12 series, robotic gastric surgery has been shown to be a safe and feasible method. However, a considerable number of studies are composed of early‐stage gastric cancer cases and there seems to be a lack of randomized controlled studies. Conclusions Large prospective randomized studies are still required in order to demonstrate the exact benefits of robotic surgery and its effects on survival in gastric cancer. Copyright © 2013 John Wiley & Sons, Ltd.